(2a+3b)(5a-2b)=0

Simple and best practice solution for (2a+3b)(5a-2b)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2a+3b)(5a-2b)=0 equation:


Simplifying
(2a + 3b)(5a + -2b) = 0

Multiply (2a + 3b) * (5a + -2b)
(2a * (5a + -2b) + 3b * (5a + -2b)) = 0
((5a * 2a + -2b * 2a) + 3b * (5a + -2b)) = 0

Reorder the terms:
((-4ab + 10a2) + 3b * (5a + -2b)) = 0
((-4ab + 10a2) + 3b * (5a + -2b)) = 0
(-4ab + 10a2 + (5a * 3b + -2b * 3b)) = 0
(-4ab + 10a2 + (15ab + -6b2)) = 0

Reorder the terms:
(-4ab + 15ab + 10a2 + -6b2) = 0

Combine like terms: -4ab + 15ab = 11ab
(11ab + 10a2 + -6b2) = 0

Solving
11ab + 10a2 + -6b2 = 0

Solving for variable 'a'.

Factor a trinomial.
(5a + -2b)(2a + 3b) = 0

Subproblem 1

Set the factor '(5a + -2b)' equal to zero and attempt to solve: Simplifying 5a + -2b = 0 Solving 5a + -2b = 0 Move all terms containing a to the left, all other terms to the right. Add '2b' to each side of the equation. 5a + -2b + 2b = 0 + 2b Combine like terms: -2b + 2b = 0 5a + 0 = 0 + 2b 5a = 0 + 2b Remove the zero: 5a = 2b Divide each side by '5'. a = 0.4b Simplifying a = 0.4b

Subproblem 2

Set the factor '(2a + 3b)' equal to zero and attempt to solve: Simplifying 2a + 3b = 0 Solving 2a + 3b = 0 Move all terms containing a to the left, all other terms to the right. Add '-3b' to each side of the equation. 2a + 3b + -3b = 0 + -3b Combine like terms: 3b + -3b = 0 2a + 0 = 0 + -3b 2a = 0 + -3b Remove the zero: 2a = -3b Divide each side by '2'. a = -1.5b Simplifying a = -1.5b

Solution

a = {0.4b, -1.5b}

See similar equations:

| 8(2w-6)+4(-1-5w)=o | | (5y-3)(y+2)=0 | | 2.3=1.7+m | | 25=x^2+36 | | y-5=4 | | 2x-14=3(x+3)(x+3)-8x^2 | | y=6x+2 | | -6(x-2)+4(3-6x)=36 | | y^2-6+3y=4(y-5)(y-5)-12 | | (7y-1)(2y-3)=0 | | y^2=21 | | 3x+35=7(x+5)-4x | | -75+10x=105 | | 2x^2=228 | | -75+10x=05 | | .5(y+4)(y+4)-6(y+3)=7 | | 3(x-2)=9x-9-6x | | 3(x-2)=6x-4-3x | | 0=4x^2+19x-54 | | 3x-9=2x-4(x-1) | | m^2=48 | | 3x^2-6x+5=-2(x+1)-10 | | h^2+4=40 | | 3x+5=10x+26 | | 12u^2+30u=0 | | x^2+(x-3)(x+3)=65 | | h^2=36 | | =5x^2+19x-54 | | -29.5+0.1p=0.9p+5.3 | | m^2-11m-12=0 | | 2-(4x+7)=3+2(x+2) | | x+2=8x |

Equations solver categories